When Art meets Computer Science: a systematic review about technologies and user interaction in adaptive digital museums and archives - Oliveira, Enzo Rigazzo; Schuina, Gabriel José do Amaral; Pereira, Vinícius Carvalho; Aranha, Renan Vinicius (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2025: Proceedings of the 31st Brazilian Symposium on Multimedia and the WebDO - 10.5753/webmedia.2025.15995, 2025)
The digitization of artistic productions, or their creation in a natively digital format, has expanded their scope beyond original intentions, bringing them into close interaction with software-related aspects. In this context, the dissemination, preservation, and access to such works, especially within digital museums and digital archives, are inevitably influenced by the quality of the underlying software. Considering the inherent challenges at the intersection of Digital Humanities and Computing, particularly the need for user-centered and customizable experiences to effectively manage large, heterogeneous collections, this article presents a systematic literature review focused on adaptive, personalized, and customizable digital museums and archives. The review aims to identify the main purposes of these systems, the technologies employed in their construction and maintenance, and the interaction approaches proposed for users. Using a systematic protocol, searches were conducted across ACM Digital Library, IEEE Xplore, Science Direct, and Scopus, resulting in the analysis of 21 studies. Based on the analysis of studies, we discuss trends, challenges, and opportunities for the design and development of adaptive digital museums and archives, such as the limited incorporation of Human-Computer Interaction and Software Engineering principles and the need for greater standardization in the development of adaptive digital archives.